A New Hybrid Algorithm for λ-Strict Asymptotically Pseudocontractions in 2-Uniformly Smooth Banach Spaces - Xin-dong Liu; Shih-sen Chang (Abstract and Applied Analysis)
A new hybrid projection algorithm is considered for a λ-strict asymptotically pseudocontractive mapping. Using the metric projection, a strong convergence theorem is obtained in a uniformly convex and 2-uniformly smooth Banach spaces. The result presented in this paper mainly improves and extends the corresponding results of Matsushita and Takahashi (2008), Dehghan (2011) Kang and Wang (2011), and many others.